A Design Approach for Recording Programs in Android Set-top Box - Jing Dai; Kewen Xia; Zhong Hua; Zhiqiang Kou (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In order to satisfy the individual needs of consumers for recording TV programs in some different ways, an improved scheme is presented to implement Personal Video Recorder (PVR) function in Android set-top box (STB). As for live TV programs, there are three alternative ways which are continuous recording, timer recording and time-shifting recording being designed. As for TV programs in the future, the way of scheduled recording is designed. Namely, monitor task in the background is checked by the updating of Time and Date Table (TDT) in accordance with Electronic Program Guide (EPG) information. The results show that this scheme is effective and feasible, and it enriches the interface function between TV and consumers. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3928